Selenium in Saliva and Impact on Health - (:unkn) unknown (Royal Society of Chemistry, 2015)
Saliva has important functions in maintaining oral and dental health. In recent years, analyses of saliva have gained importance due to the ready availability of noninvasive methods. Besides the many functions of saliva its antioxidant content protects oral mucosa against oxidative damage. Various diseases have been shown to be related with the impaired oxidant-antioxidant balance in saliva. Selenium, a trace element involved in the structure of antioxidant enzymes glutathione peroxidase and thioredoxin reductase, contributes to the antioxidant activity of the organism. However, contradictory results were reported on the effect of selenium on dental caries. In this chapter the studies investigating the effects of selenium on dental health and the importance of salivary selenium has been reviewed. © The Royal Society of Chemistry 2015.